Systemic Immune-Inflammatory Index as a Prognostic Biomarker in Patients with Heart Failure: A Comprehensive Analysis - Aihaidan Abudouwayiti MD; Yanxiao Li MD; Tumaresi Tuerxun MD; Muyashaer Abudurexiti MD; Dongqin Duan MD; Ying-Ying Zheng PhD; Ailiman Mahemuti PhD (Clinical and Applied Thrombosis/Hemostasis)
Objective This study aimed to assess the prognostic significance of the Systemic Immune-Inflammatory Index (SII) in chronic heart failure (CHF) patients and evaluate its potential as a predictive biomarker. Methods A retrospective analysis was conducted on 2748 CHF patients from the First Affiliated Hospital of Xinjiang Medical University from 2012 to 2022. The primary outcome was all-cause mortality (ACM), with readmission rates as secondary endpoints. An optimal SII cutoff value of 916.68 was determined for predicting ACM. Results Elevated SII levels were significantly correlated with an increased risk of ACM in CHF patients across all left ventricular ejection fraction (LVEF) categories. The high SII group had a 43.8% increased risk of ACM compared to the low SII group. Conclusion SII is a significant prognostic biomarker in CHF, independent of traditional risk factors, highlighting its importance in risk stratification and clinical decision-making, and necessitating further investigation in prospective studies.